Constructing the charisma of khruba (Venerable monks) in contemporary Thai society - Pisith Nasee (2018)
© Center for Southeast Asian Studies, Kyoto University. Khruba (venerable monks) have consistently played a meaningful role in local Buddhist communities of Northern Thai culture for generations. While today’s khruba continue to represent themselves as followers of Khruba Siwichai and Lan Na Buddhism, in fact over the past three decades they have flourished by adopting heterogeneous beliefs and practices in the context of declining influence of the sangha and popular Buddhism. In order to respond to social and cultural transformations and to fit in with different expectations of people, modern khruba construct charisma through different practices besides the obvious strictness in dhamma used to explain the source of khruba’s charisma in Lan Na Buddhist history. The ability to integrate local Buddhist traditions with the spirit of capitalism-consumerism and gain a large number of followers demonstrates that khruba is still a meaningful concept that plays a crucial role in modern Buddhist society, particularly in Thailand. By employing concepts of charisma, production of translocalities, and popular Buddhism and prosperity religion, it can be argued that khruba is steeped in local knowledge, yet the concept has never been linear and static. Modern khruba can be interpreted and consumed in many ways by diverse groups of people. This is also considered a key success of modern khruba and their proliferation during the past three decades in Thailand. Data were collected in 2015–16 through in-depth interviews and participatory observation as part of the author’s PhD dissertation at Chiang Mai University, Thailand.